A comprehensive approach to small and large-scale effects of earthquake motion variability. (September 2018) - Tomasin, M.; Domaneschi, M.; Guerini, C.; Martinelli, L.; Perotti, F.
Highlights: Effects of the spatial variability of earthquake input motion. Single rigid foundation and multiple foundations. Rocking effects in the isolation system of special structures. Influence of the rotational components in structures having tall members. Case studies: base isolated nuclear reactor building and cable-supported bridge structures. Abstract: This work deals with the evaluation of the effects of the spatial variability of earthquake input motion on the dynamic response of structures. The variability of the free-field motion both over the area of a single foundation as well as over the distance between independent foundations of large structures is considered. Two significant applications of the proposed numerical procedure are presented. In the first one a base isolated nuclear reactor building is considered where the issue of the rocking excitation on the peak value of axial forces in the isolation devices and acceleration in the building structure is investigated. Extended structures having tall members are considered as second application. A cable-supported bridge model, formerly studied within a simpler representation of the seismic ground motion, serves as case study in which spatial variability acts at different scales.